The Role of Growth Hormone-Releasing Hormone and the Hypothalamic–Pituitary–Somatotropic Axis in Aging: Potential Therapeutic Applications and Risks - Oikonomakos, Ioannis; Siow, Richard; Bornstein, Stefan R.; Steenblock, Charlotte (Hormone and Metabolic Research, 2025)
Aging is marked by a gradual decline in multiple physiological functions, increasing the risk of age-related disorders. Multiple factors have been identified as contributors to aging, many of which are regulated by the hypothalamus. Growth hormone-releasing hormone (GHRH) produced in the hypothalamus is a key regulator of growth hormone (GH) secretion. With aging, both GHRH and GH levels decline, leading to muscle loss, increased fat accumulation, metabolic dysregulation, and cognitive impairments. GH replacement therapy has been explored as a potential intervention to counteract these effects; however, its long-term use is associated with significant risks, including metabolic disturbances, cardiovascular complications, and potential cancer promotion. In contrast, studies suggest that GHRH-based therapies can improve body composition, muscle strength, cognitive function, and cardiovascular health while avoiding the risks linked to direct GH administration. Additionally, preclinical findings indicate that GHRH agonists may offer cardioprotective and immunomodulatory benefits. In this review, we summarize current knowledge on the roles of GHRH and GH in aging, highlight the limitations of GH-based therapies, and discuss the potential of GHRH-based approaches in mitigating age-related decline and improving health span.
Keywords: aging; GH; GHRH; hypothalamus; metabolism